PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT MARGAMAS CITRATAMA DI JAKARTA UTARA - Herdiana Putri; Dewi Sartika (Al Hasanah Barokah Foundation, 2025)
This study aims to determine the effect of Work Discipline and Physical Work Environment on Employee Performance at PT. Margamas Citratama in North Jakarta. This study uses a quantitative method with an associative approach. The sampling technique used is simple random sampling. The sample in this study was determined using the saturated sample formula, from a total population of 60 employees, a sample of 60 respondents was obtained. The data collection technique was carried out by distributing questionnaires. The data analysis technique used multiple linear regression analysis, classical assumption tests, hypothesis tests, and coefficients of determination. The results showed that Work Discipline had a positive and significant effect on Employee Performance, with the results of the t_count = 8.168> t_table = 1.675 and a significance value <0.05, then H₁ was accepted. The Physical Work Environment showed a positive but insignificant effect on Employee Performance, with a t_count = 5.835> t_table = 1.675 and a significance value> 0.05, then H₂ was accepted. Simultaneously, Work Discipline and Physical Work Environment have a positive and significant effect on Employee Performance, with a multiple regression equation of Y = 1.359 + 0.027 X₁ + 0.009 X₂. The coefficient of determination R² of 0.710 indicates that 71% of the variation in Employee Performance can be explained by the two independent variables. The results of the F test obtained a value of F_count = 69.679 > F_table = 3.18, so H₃ is accepted.